Impact of Paraesophageal Hernia Repair on Respiratory Function: A Systematic Review - Myers, Dominick; Jacobson, Xander; Dale, Matthew; Sahasranaman, Venket; Nandipati, Kalyana (Frontiers in Surgery, 2021)
Background and Objectives Surgical repair of hiatal and paraesophageal hernia is widely accepted for the treatment of gastroesophageal reflux symptoms. The respiratory benefit of this surgery is less clear. The objective of this review is to quantify the benefit to pulmonary function and subjective dyspnea of paraesophageal hernia repair with the aim of refining the indications and contraindications for elective paraesophageal hernia repair. Methods Articles were gathered from systematic searches of the Medline Complete Database via the Creighton University Health Sciences Library literature search services. Publications with both pre and postoperative pulmonary function data or both pre and postoperative subjective dyspnea data with regards to surgical paraesophageal hernia repair were included. Results Six studies were included in this review. The majority of studies in this review show improvement in pulmonary function postoperatively with regards to FEV1, FVC, and VC when stratified by % intrathoracic stomach (ITS), particularly in groups >50% ITS. No significant change was seen in postoperative DLCO or FEV1/FVC. Conclusion Paraesophageal hernia repair has shown to improve pulmonary function both objectively and subjectively. This review was limited by the paucity of literature on the subject as well as the lack of a standardized method for measurement of %ITS.